Earth Observation - Rustamov, Rustam B.; Salahova, Saida E.; Rustamov, Rustam B.; Salahova, Saida E. (IntechOpen, 2012)
Today, space technology is used as an excellent instrument for Earth observation applications. Data is collected using satellites and other available platforms for remote sensing. Remote sensing data collection detects a wide range of electromagnetic energy which is emitting, transmitting, or reflecting from the Earth's surface. Appropriate detection systems are needed to implement further data processing. Space technology has been found to be a successful application for studying climate change, as current and past data can be dynamically compared. This book presents different aspects of climate change and discusses space technology applications.
English
Keywords: Other technologies & applied sciences; Space science